Selectively oxidised vertical cavity surface emitting lasers with 50% power conversion efficiency - Geib, K. M., author; Kilcoyne, S. P., author; Schneider, R. P., author; Choquette, K. D., author; Lear, Kevin L., author; IEE, publisher (Colorado State University. Libraries, 1995)
Index-guided vertical cavity top-surface emitting laser diodes have been fabricated from an all epitaxial structure with conducting mirrors by selective lateral oxidation of AlGaAs. Low voltage, a 78% slope efficiency, and a 350μA threshold current in a single device combine to yield a maximum power conversion efficiency of 50% at less than a 2mA drive current. The device operates in a single mode up to 1.5mW.
Keywords: lasers; vertical cavity surface emitting lasers